Designing and prototyping of a transverse flux machine in soft magnetic composite using milling and turning techniques - Mannerhagen, Felix (My University, 2017)
In this thesis a polyphase claw pole machine has been designed, prototyped and verified through measurements. The FE-calculation model have been verified against analytical calculations, there after the design have been changed through an iterative process to a more optimised design. The machine have then been built in a soft magnetic composite, using milling and turning techniques. The techniques used to minimise the chapped edges is described. The FE-calculated machine model is then verified against equal circuit parameters measurements, with a relative small error.
Keywords: Elkraftteknik; Electric power engineering